PENGARUH PRE-TEST TERHADAP TINGKAT PEMAHAMAN MAHASISWA PROGRAM STUDI ILMU POLITIK PADA MATA KULIAH ILMU ALAMIAH DASAR - Fadhlya Adri, Rantih (Menara Ilmu, 2020)
Abstract: This study aims to determine the effect of pre-test on the level of understanding of Political Science Study Program students in Basic Natural Sciences courses. there are two classes that are divided into experimental and control classes. The experimental class is given a pretest, while the control class is not given a Pre-Test, but at the end of the lecture is given the same Post-Test. The results showed that there were significant differences between the control class and the experimental class on the level of student understanding. This is based on differences in the average post-test results that are significantly different, where the experimental class has a higher score Keywords: Pre-Test, Basic Natural Sciences